Quality of fresh and chilled-stored raccoon dog semen and its impact on artificial insemination efficiency. Issue 1 (December 2016) - Jarosz, Łukasz; Grądzki, Zbigniew; Kalinowski, Marcin; Laskowska, Ewa
Abstract Background The aim of the study was to evaluate the quality of fresh raccoon dog semen and raccoon dog semen stored at 4 °C. The qualitative evaluation was based on apoptosis in the sperm cells, which was tested by the Annexin V/Pi assay, the TUNEL method and JC-1. In addition, the suitability of the semen for insemination and its effect on reproduction in females were determined in relation to the time of storage. Results During cold storage of the semen, in the samples from all groups a gradual decrease was noted in the percentage of live cells, and an increase in the percentage of cells with abnormal morphology, exhibiting changes typical of late-stage apoptosis (V+ /PI+ ), and of necrotic cells (V− /PI+ ). There was a significant increase in the percentage of ApoBrDu + sperm cells, while the mitochondrial membrane potential of the sperm decreased significantly after 12 h of storage at 4 °C in the case of lower-quality semen and after 48 h in the case of semen of good quality. As the percentage of sperm with DNA and cell membrane damage increased and the mitochondrial membrane potential decreased, there was an increase in AspAT and acrosin activity. The increase in the percentage of apoptotic sperm in the raccoon dog semen stored at 4 °C resulted in a decrease in the number of females with cubs. Conclusions Identification of apoptotic changes in sperm by flow cytometry using the annexin assay, the TUNEL assay and evaluation of mitochondrial membrane potential can be recommended for determination of the suitability of raccoon dog semen for artificial insemination. The study shows that fresh raccoon dog semen should not be used for insemination more than 48 h after collection in the case of semen of very high quality, or after more than 24 h in the case of semen of poorer quality. Cytometric methods of semen analysis should also be used to evaluate various extenders of raccoon dog semen and methods of cryopreservation in terms of ensuring sperm viability, fertilization capacity, and suitability for insemination.